Nutrient Deficiency Tolerance in Citrus Is Dependent on Genotype or Ploidy Level - Oustric, Julie; Morillon, Raphaël; Luro, François; Herbette, Stéphane; Martin, Paul; Giannettini, Jean; Berti, Liliane; Santini, Jérémie (Frontiers in Plant Science, 2019)
Plants require essential minerals for their growth and development that are mainly acquired from soil by their roots. Nutrient deficiency is an environmental stress that can seriously affect fruit production and quality. In citrus crops, rootstock/scion combinations are frequently employed to enhance tolerance to various abiotic stresses. These tolerances can be improved in doubled diploid genotypes. The aim of this work was to compare the impact of nutrient deficiency on the physiological and biochemical response of diploid (2x) and doubled diploid (4x) citrus seedlings: Volkamer lemon, Trifoliate orange  Cleopatra mandarin hybrid, Carrizo citrange, Citrumelo 4475. Flhorag1 (Poncirus trifoliata + and willow leaf mandarin), an allotetraploid somatic hybrid, was also included in this study. Our results showed that depending on the genotype, macronutrient and micronutrient deficiency affected certain physiological traits and oxidative metabolism differently. Tetraploid genotypes, mainly Flhorag1 and Citrumelo 4475, appeared resistant compared to the other genotypes as indicated by the lesser decrease in photosynthetic parameters (Pnet, Fv/Fm and Gs) and the lower accumulation of oxidative markers (MDA and H202) in roots and leaves, especially after long-term nutrient deficiency. Their higher tolerance to nutrient deficiency could be explained by better activation of their antioxidant system. For the other genotypes, tetraploidization did not induce greater tolerance to nutrient deficiency.